Demographics and regional trends of ischemic heart disease-related mortality in older adults in the United States, 1999-2020. - Fakhar Latif; Muhammad Moiz Nasir; Wajeeh Ur Rehman; Mohammed Hamza; Jishanth Mattumpuram; Komail Khalid Meer; Helme Silvet; Alon Yarkoni; Mouhamed Amr Sabouni; Nabil Braiteh; Keyoor Patel; Abdulqadir J Nashwan (PLoS ONE, 2025)
Background Ischemic heart disease (IHD) has a significant impact on public health and healthcare expenditures in the United States (US). Methods We used data from the CDC WONDER database from 1999-2020 to identify trends in the IHD-related mortality of patients ≥ 75 years in the US. AAMRs per 100,000 population and APC were calculated and categorized by year, sex, race, and geographic divisions. Results Between 1999 and 2020, a total of 8,124,568 IHD-related deaths were recorded. Notable declines in AAMR were observed from 1999 to 2014 (APC: -3.86) and from 2014 to 2018 (APC: -2.55), with an overall increase from 2018 to 2020 (APC: 3.76). Older men consistently demonstrated higher AAMRs than older females, with AAMRs for both sexes decreasing steadily from 1999 to 2018 and increasing in 2020. When stratified by race/ethnicity, Whites (1931.7) had the highest AAMR, followed by Blacks (1836.5), American Indians (1510.5), Hispanics (1464.4), and Asians (1093.6). Furthermore, nonmetropolitan areas (2015.2) showed greater AAMRs than metropolitan areas (1841.8). The ≥ 85-year group consistently exhibited higher IHD-related mortality rates compared to the 75-84 years group. In comparison, the older group [≥75 years] (1873.0) consistently exhibited higher IHD-related AAMRs than the younger group [<75 years] (64.0) throughout the study, showing a significant disparity. Chronic IHD (1552.0) consistently showed the highest AAMRs throughout the study, surpassing myocardial infarction (515.6), other ischemic heart diseases (24.0), and angina pectoris (5.6). Conclusion Targeted interventions and resource allocation are crucial for areas with high IHD-related mortality. Public health policies should address demographic and geographical disparities, with further research for effective strategies.